Mesenchymal Stem Cell Protects Injured Renal Tubular Epithelial Cells by Regulating mTOR-Mediated Th17/Treg Axis - Luo, Yongsheng; Guo, Jingjing; Zhang, Pingbao; Cheuk, Yin Celeste; Jiang, Yamei; Wang, Jiyan; Xu, Shihao; Rong, Ruiming (Frontiers in Immunology, 2021)
The increase in T helper 17 cell (Th17)-mediated pro-inflammatory response and decrease in regulatory T cell (Treg)-mediated anti-inflammatory effect aggravate renal tubular epithelial cell (RTEC) injury. However, increasing evidence indicated that mesenchymal stem cell (MSC) possessed the ability to control the imbalance between Th17 and Treg. Given that Th17 and Treg are derived from a common CD4+ T cell precursor, we summarize the current knowledge of MSC-mediated inhibition of the mammalian target of rapamycin (mTOR), which is a master regulator of CD4+ T cell polarization. During CD4+ T cell differentiation, mTOR signaling mediates Th17 and Treg differentiation via hypoxia-inducible factor-1α (HIF-1α)-dependent metabolic regulation and signaling pathway, as well as mTOR-mediated phosphorylation of signal transducer and activator of transcription (STAT) 3 and 5. Through interfering with mTOR signaling, MSC restrains CD4+ T cell differentiation into Th17, but in turn promotes Treg generation. Thus, this review indicates that MSC-mediated Th17-to-Treg polarization is expected to act as new immunotherapy for kidney injury.